1997
DOI: 10.1046/j.1365-313x.1997.12061387.x
|View full text |Cite
|
Sign up to set email alerts
|

Slowly activating vacuolar channels can not mediate Ca2+‐induced Ca2+ release

Abstract: In order to test the hypothesis that slowly activating vacuolar (SV) channels mediate Ca2+‐induced Ca2+ release the voltage‐ and Ca2+‐dependence of these K+ and Ca2+‐ permeable channels were studied in a quantitative manner. The patch‐clamp technique was applied to barley (Hordeum vulgare L.) mesophyll vacuoles in the whole vacuole and vacuolar‐free patch configuration. Under symmetrical ionic conditions the current‐voltage relationship of the open SV channel was characterized by a pronounced inward rectificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
115
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 0 publications
9
115
3
Order By: Relevance
“…It was suggested that the SV channel would also carry e¥ux of Ca 2+ from the vacuole, in a process of Ca 2+ -induced Ca 2+ release, but recent more detailed study of the voltage conditions for activation of the SV channel in barley mesophyll vacuoles argues against this. Pottosin et al (1997) found that the open probability of the SV channel depended on the electrochemical gradient for Ca 2+ across the tonoplast. At the equilibrium potential for Ca 2+ the open probability was as low as 0.4%, and declined further in conditions favouring Ca 2+ release from the vacuole; essentially the channel opened signi¢cantly only when the gradient was such as to drive Ca 2+ into the vacuole.…”
Section: (D) Anion Channels In the Plasmalemmamentioning
confidence: 99%
“…It was suggested that the SV channel would also carry e¥ux of Ca 2+ from the vacuole, in a process of Ca 2+ -induced Ca 2+ release, but recent more detailed study of the voltage conditions for activation of the SV channel in barley mesophyll vacuoles argues against this. Pottosin et al (1997) found that the open probability of the SV channel depended on the electrochemical gradient for Ca 2+ across the tonoplast. At the equilibrium potential for Ca 2+ the open probability was as low as 0.4%, and declined further in conditions favouring Ca 2+ release from the vacuole; essentially the channel opened signi¢cantly only when the gradient was such as to drive Ca 2+ into the vacuole.…”
Section: (D) Anion Channels In the Plasmalemmamentioning
confidence: 99%
“…The SV channel is permeable to both monovalent and divalent cations and is activated by cytosolic Ca 2+ and positive vacuolar voltage (Hedrich and Neher, 1987;Ward and Schroeder, 1994;Pottosin et al, 1997Pottosin et al, , 2001. The FV channel is permeable for monovalent cations only, is activated by large voltages of either sign, and is inhibited by divalent cations from either side of the membrane Brüggemann et al, 1999aBrüggemann et al, , 1999b.…”
mentioning
confidence: 99%
“…Absence of Ca 2+ -activated SV currents was confirmed in an independent study (Ranf et al, 2008). SV channels are downregulated by vacuolar Ca 2+ (Pottosin et al, 1997;Pei et al, 1999), but can allow Ca 2+ transport from the vacuole to the cytoplasm (Bewell et al, 1999), which is for example illustrated by "tail" currents recorded in pure CaCl 2 gradients (Ward et al, 1995). SV channels are ubiquitous and have been found in all plant vacuoles, but in spite of their broad distribution in plant vacuoles, their physiological functions are not yet understood.…”
Section: Vacuolar Channelsmentioning
confidence: 68%